Melatonin in perioperative medicine: Current perspective - Maitra, Souvik (Medknow Publications & Media Pvt Ltd, 2013)
Melatonin, a new addition to the armamentarium of anesthesiologist, has some unique properties that are highly desirable in routine peri-operative care. Available clinical data show that preoperative melatonin is as effective as benzodiazepines in reducing preoperative anxiety with minimal action on psychomotor performance and sleep wake cycle. It may be considered as a safe and effective alternative of benzodiazepines as preoperative anxiolytic. It may have opioid sparing effect, may reduce intraocular pressure, and have role in prevention of postoperative delirium. The short-term administration of melatonin is free from significant adverse effects also.